A Life Committed to Leadership: Life Lessons from Margaret Chase Smith and Outcomes That Would Please Her - Godfrey, Linda (Maine Policy Review, 2018)
Seeing Margaret Chase Smith during the GOP Convention in 1964 triggered an epiphany for the teenage Linda Cross Godfrey on women as leaders. In this essay, the author describes what she learned from Margaret Chase Smith during the friendship that developed between them.
Keywords: leadership; Margaret Chase Smith; women leaders